Correlation between Hemostasis Profile and Sepsis Outcome - Sisi Melansi; Eny Rahmawati; Susilawati Susilawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Sepsis is an organ dysfunction caused by infection. Excessive cytokine activation, which causes hemostasis disorder is rated by Prothrombin Time (PT), activated Partial Thromboplastin Time (aPTT), fibrinogen, and D-dimer tests. Hemostasis disorder can affect several sepsis outcomes (mortality and duration of treatment period). This study aimed to determine the correlation between hemostasis profile and sepsis outcome. This research was an analytical-observational with retrospective cohort study design with subjects consisting of 76 sepsis patients at Dr. Mohammad Hoesin Hospital, Palembang. The data were obtained by medical record observation and analyzed by Chi-Square and Spearman tests. From 76 sepsis patients, 76.7% of subjects had normal PT; 88.2% had normal aPTT; 71.1% had elevated fibrinogen, and 100% had elevated D-dimer. The patients' sepsis outcomes showed that 67.1% survived, and 32.9% has died, and the duration of the treatment period without much differences is as long as â‰¤ 12 days and > 12 days. The statistical analysis showed that there was no significant relationship between PT, mortality, duration of the treatment period (p=1.000; p=0.418), between aPTT, mortality, duration of the treatment period (p=0.709; p=0.480), between fibrinogen, mortality, duration of the treatment period (p=0.350; p=1.000), and there was a weak negative correlation between D-dimer mortality and duration of the treatment period (p=0.459; p=0.939). It could be concluded that there was no significant correlation between hemostasis profile and sepsis outcome.